Examining Technical efficiency of Wood-Based Industries in Ethiopia - Kaba, Gemechu; Belachew, Azmera; Ababu, Tesfanesh; Gelan, Asfaw (Rescollacom (Research Collaborations Community), 2024)
Technical efficiency is crucial for the advancement and growth of contemporary enterprises and is a major area of policy concern in many countries. Numerous pieces of evidence suggest that Ethiopia's industries, particularly those depend on wood were not operating as efficient as they should be. As a result, the country is not benefiting as much from the sector as it ought to, and it is now compelled to import wooden products at a higher cost in foreign exchange. Therefore, to examine the technical efficiency of the industries; four purposively selected main cities such as Addis Ababa, Hawassa, Jima and Bahir Dar were selected. From these cities, information was collected, analyzed, and the results were obtained. The result shows that the technical efficiency of Ethiopia's wood industries is lower than expected. Out of a total of 170, about 149 (87.6 %) of the furniture workshops are technically inefficient. This is because workers working in the wood industries are less educated. In addition to this lack of on-the-job training, lack of modern machineries and insufficient skills to use them properly, inconvenient production and sales area, shortage and quality of raw materials, insufficient capital, lack of market connection, have been shown to be the reasons. Therefore, to improve the technical efficiency of the industries, it is better to have continuous vocational training, loan support so that they can get and use better machines, as well as convenient manufacturing, product display and sales, improving and facilitating market linkages.